The Urgency of the Role and Concept of Digital Literacy in Education in the Disruption Era (21st Century) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
In addition to entering the era of globalization with the start of the AEC (Asian Economic Community) and the incessant life of the 21st century, the world is currently experiencing super- fast changes marked by a new era or referred to as the era of the industrial revolution 4.0. This high competence is of course a special concern for education as the main guard for competency development. One of the most important components in this field is of course educators. An educator in this era is required to be able to make digital natives (children who know technology from birth) as human beings who will not lose and make mistakes in taking steps and in utilizing existing technology, bearing in mind that in addition to great benefits, technology is quite a threat to the development of students. Educators must be able to select and filter technology and insert value into their learning with digital literacy. So, of course this is of particular concern so that educators have this digital literacy competence. Strengthening literacy, numeracy and technological adaptation are important efforts to improve the quality of human resources in the Digital Age and the Disruption Era. Indonesia is very far behind other countries in terms of this capability. The government as well as related parties (Schools, Universities, Education Quality Assurance Institutions, and Parents) must participate in strengthening literacy, numeracy, and technology adaptation for students and educators in Indonesia. One of the activities is integrating literacy, numeracy and technology activities in learning either at school or at home.